2013
DOI: 10.1002/pssc.201200523
|View full text |Cite
|
Sign up to set email alerts
|

Irradiation study on Srn+1TinO3n+1 Ruddlesden‐Popper phases synthesized by hot‐forging

Abstract: The hot‐forging technique was used to obtain both the n = 2 (Sr3Ti2O7) and n = ∞ (SrTiO3) members of Ruddlesden‐Popper phase Srn+1TinO3n+1. Pure phase and high density (>95% theoretical) materials were achieved using this technique. These polycrystalline samples were irradiated with 200 keV He ions to a fluence of 2×1021 ion/m2 (corresponding to a peak dose at 5 dpa) at room temperature to study radiation damage effects. Microstructural investigation on pristine and irradiated samples was performed using gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…One study did compare the radiation tolerance of SrTiO 3 and Sr 3 Ti 2 O 7 , which can be viewed as STO with the highest density of RP faults possible within the material. 10 This study found that the second material, effectively containing a high density of RP faults, amorphized at a dose of 5 dpa while the stoichiometric STO did not. This suggests an important role of the RP faults in the radiation damage evolution of the material, but that role is far from clear.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…One study did compare the radiation tolerance of SrTiO 3 and Sr 3 Ti 2 O 7 , which can be viewed as STO with the highest density of RP faults possible within the material. 10 This study found that the second material, effectively containing a high density of RP faults, amorphized at a dose of 5 dpa while the stoichiometric STO did not. This suggests an important role of the RP faults in the radiation damage evolution of the material, but that role is far from clear.…”
Section: Introductionmentioning
confidence: 73%
“…As mentioned in the introduction, one study compared the radiation tolerance of stoichiometric SrTiO 3 with the Ruddlesden-Popper phase Sr 3 Ti 2 O 7 . 10 That study found that the RP phase material was much more susceptible to amorphization than the stoichiometric material, suggesting that the RP faults enhance amorphization. This is consistent with our results which show that the RP faults themselves preferentially amorphize.…”
Section: Discussionmentioning
confidence: 95%
“…Individual RP faults were observed to amorphize more readily than the surrounding matrix, which was attributed to the attraction of radiation-induced point defects to the RP faults [332]. When a high density of RP faults is present, such as in the case of the RP phase, Sr 3 Ti 2 O 7 , the material amorphizes significantly faster than stoichiometric SrTiO 3 [333].…”
Section: Amorphization In Perovskitesmentioning
confidence: 99%
“…The adsorption products are easily converted into a stable titanate ceramic by one-step sintering in argon at 1200°C. Tang et al (2013) reported on the effect of irradiation on Sr n+1 Ti n O 3n+1 Ruddlesden-Popper phases synthesized by hot forging. Radiation damage effects in the Ruddlesden-Popper phases Sr n+1 Ti n O 3n+1 with n = 2 and ∞ obtained by a hot-forging route has been investigated using 200 keV He ion irradiation at room temperature.…”
Section: Titanatesmentioning
confidence: 99%